2016
DOI: 10.1556/004.2016.028
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus pentosus expressing porcine lactoferrin elevates antibacterial activity and improves the efficacy of vaccination against Aujeszky’s disease

Abstract: In this study, Lactobacillus pentosus expressing porcine lactoferrin (pLF) was tested for in vitro antibacterial activity and for its ability to enhance immunity induced by an orally administered Aujeszky's disease virus (ADV) vaccine. The cDNA encoding N-terminus of pLF was cloned into a Lactobacillus-specific plasmid to produce L. pentosus pLF expressing transformants (pPG612.1-pLF-N/L. pentosus). The antimicrobial activity of the recombinant pLF protein inhibited bacterial growth in vitro. The supernatant o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Lfcin-Lfampin could be used as a replacement for antibiotic therapy for sepsis, taking advantage of its selective antimicrobial action and probiotic effect as an immune modulator [115,117]. Recombinant Lactobacillus strains expressing Lf [126,127] may be future strategies to prevent and combat high-risk human infections, such as neonatal necrotizing enterocolitis [128]. As documented in murine models and clinical trials, pharmaceutical preparations containing bLf and probiotics or Lf-producing probiotic strains have been effective to combat vulvovaginal infections caused Candida albicans , Gardnerella vaginalis, or Atopobium vaginalis by restoring the microbiota in vulvovaginal tract [129,130,131].…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Lfcin-Lfampin could be used as a replacement for antibiotic therapy for sepsis, taking advantage of its selective antimicrobial action and probiotic effect as an immune modulator [115,117]. Recombinant Lactobacillus strains expressing Lf [126,127] may be future strategies to prevent and combat high-risk human infections, such as neonatal necrotizing enterocolitis [128]. As documented in murine models and clinical trials, pharmaceutical preparations containing bLf and probiotics or Lf-producing probiotic strains have been effective to combat vulvovaginal infections caused Candida albicans , Gardnerella vaginalis, or Atopobium vaginalis by restoring the microbiota in vulvovaginal tract [129,130,131].…”
Section: Practical Implicationsmentioning
confidence: 99%
“…In addition, Lactobacillus pentosus has been used to express porcine LF (PLF), and L. pentosus/PLF supplementation has been described to elevate antibacterial activity and improve the efficacy of vaccination against Aujeszky's disease in a mouse model. This report also suggests that recombinant L. pentosus could provide both the beneficial characteristics of lactic acid bacteria and the biological activity of lactoferrin [14]. Finally, L. plantarum has been employed for expression of PLF and was used as a feed additive in the daily diet of weaned piglets, and addition of recombinant L. plantarum/PLF led to a significant increase in average daily gain and feed intake, improved feed efficiency, and reduced incidence of diarrhea in these piglets [15].…”
Section: Introductionmentioning
confidence: 61%
“…Similarly, Liao et al developed a BLF-expressing L. casei strain and found that the recombinant L. casei /pPG612.1-BLF acted as an enhancer, improving the immunity of vaginal mucosa against the intrusion of Candida albicans in a murine model [ 104 ]. Moreover, L. pentosus was engineered to express PLF, and this recombinant PLF-expressing probiotic strain was demonstrated to increase the antibacterial activity in vitro and improve the efficacy of vaccination against Aujeszky’s disease in a mouse model [ 105 ].…”
Section: Combining Lf With Probiotics To Fight Bacterial Infections O...mentioning
confidence: 99%